Social context affects thermoregulation but not activity level during avian immune response. (18th December 2018) - Vaziri, Grace J; Johny, Manju M; Caragea, Petruţa C; Adelman, James S
Abstract: Determining how an animal's social context alters its immune responses will help us understand how pathogens impact individual health and spread within groups. Several studies have shown that group-housed animals can suppress components of the acute phase immune response, specifically sickness behaviors like lethargy. However, we do not know whether individuals alter sickness behaviors or other components of the acute phase response, including thermoregulation, in response to the infection status of other group members. We used automated radio telemetry on captive house sparrows ( Passer domesticus ) to test whether sickness behaviors and thermoregulation differed during immune challenge under 2 social contexts: 1) all of the flock inoculated with lipopolysaccharide (LPS), a non-replicating component of gram-negative bacterial cell walls, or 2) half of the flock inoculated. We predicted that with half of the flock inoculated, LPS-treated birds would be under more pressure to maintain competitive behaviors, so would suppress components of the acute phase response. As we predicted, LPS-inoculated birds showed less pronounced heterothermia (fever) when housed with a mixture of inoculated and healthy flockmates. In contrast, LPS-inoculated birds exhibited similar degrees of lethargy regardless of the infection status of their flockmates. Our results show that the infection status of an individual's social group did exert an effect on the acute phase response but surprisingly did not impact the expression of lethargy, a canonical sickness behavior. Determining the mechanisms underlying these responses will require testing additional social contexts with different ratios of infected to uninfected birds. Abstract : Infection and sickness have direct physiological costs and indirect behavioral costs. Accordingly, many animals, including birds, can mask their signs of illness around healthy individuals, behaving normally despite infection. But if everyone is sick, is it still worth masking your behavioral symptoms? We showed that house sparrows mounting an immune response do not change their behaviors based on how many other birds around them are also sick. Curiously, though, they do exhibit different fever responses.